Reply to “Comments on ‘Fortune Favors the Prepared Firm’” - Cohen, Wesley M.; Levinthal, Daniel A. (Management Science, 1997)
Joglekar, Bohl, and Hamburg (JBH) make two basic sets of criticisms of our paper (Cohen and Levinthal [Cohen, W. M., D. A. Levinthal. 1994. Fortune favors the prepared firm. Management Sci. 40 227–251.]) in their comment. First, they object to two key elements of the model structure: the relevance of the monopoly analysis and the appropriateness of modeling competition via an entry model. Second, JBH express concern over the manner in which we have modeled the updating process. With regard to the basic model structure, we argue that the initial monopoly analysis allows us to capture some important notions regarding the path dependent nature of investment in technical capabilities. Further, the analysis of competition by an entry model does not presume that an established firm takes the initiative which is one of JBH's key objections. The structure merely implies that some firm, possibly a start-up enterprise, moves first. With regard to the concerns over the modeling of updating, we acknowledge that our notation could have been clearer in some instances but that does not negate the correctness of the analysis. Furthermore, JBH's recommendations regarding the updating process have the same qualitative properties as our own specification. Indeed, at no point in their critique do JBH ever indicate how their proposed specification would change the results of our analysis.